HSP90α induces immunosuppressive myeloid cells in melanoma via TLR4 signaling. Issue 9 (16th September 2022) - Arkhypov, Ihor; Özbay Kurt, Feyza Gül; Bitsch, Rebekka; Novak, Daniel; Petrova, Vera; Lasser, Samantha; Hielscher, Thomas; Groth, Christopher; Lepper, Alisa; Hu, Xiaoying; Li, Wei; Utikal, Jochen; et al.
Abstract : Background: Tumor cells modulate host immunity by secreting extracellular vesicles (EV) and soluble factors. Their interactions with myeloid cells lead to the generation of myeloid-derived suppressor cells (MDSC), which inhibit the antitumor function of T and NK cells. We demonstrated previously that EV derived from mouse and human melanoma cells induced immunosuppressive activity via increased expression of programmed cell death ligand 1 (PD-L1) on myeloid cells that was dependent on the heat-shock protein 90α (HSP90α) in EV. Here, we investigated whether soluble HSP90α could convert monocytes into MDSC. Methods: CD14 monocytes were isolated from the peripheral blood of healthy donors, incubated with human recombinant HSP90α (rHSP90α) alone or in the presence of inhibitors of TLR4 signaling and analyzed by flow cytometry. Inhibition of T cell proliferation assay was applied to assess the immunosuppressive function of rHSP90α-treated monocytes. HSP90α levels were measured by ELISA in plasma of patients with advanced melanoma and correlated with clinical outcome. Results: We found that the incubation of monocytes with rHSP90α resulted in a strong upregulation of PD-L1 expression, whereas reactive oxygen species (ROS) and nitric oxide (NO) production as well as the expression of arginase-1, ectoenzymes CD39 and CD73 remained unchanged. The PD-L1 upregulation was blocked by anti-TLR4 antibodies and a nuclear factor-κB inhibitor. rHSP90α-treated monocytes displayed the downregulation of HLA-DR expression and acquired the resistance to apoptosis. Moreover, these monocytes were converted into MDSC as indicated by their capacity to inhibit T cell proliferation, which was mediated by TLR4 signaling as well as PD-L1 and indoleamine 2, 3-dioxygenase (IDO) 1 expression. Higher levels of HSP90α in plasma of patients with melanoma correlated with augmented PD-L1 expression on circulating monocytic (M)-MDSC. Patients with melanoma with high levels of HSP90α displayed shorter progression-free survival (PFS) on the treatment with immune checkpoint inhibitors (ICIs). Conclusion: Our findings demonstrated that soluble rHSP90α increased the resistance of normal human monocytes to apoptosis and converted them into immunosuppressive MDSC via TLR4 signaling that stimulated PD-L1 and IDO-1 expression. Furthermore, patients with melanoma with high concentrations of HSP90α displayed increased PD-L1 expression on M-MDSC and reduced PFS after ICI therapy, suggesting HSP90α as a promising therapeutic target for overcoming immunosuppression in melanoma.